تحليل منهج إعداد الكتاب التعليمي تحسين الكتابة الإعتيادية النسخة الثالثة في ضوء مبادئ إعداد الكتاب التعليمي - Fajar Aminun Najib ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2025)
This study aims to analyze the methodology of developing the Tahsinul Kitabah al-I‘tiyādiyyah textbook (third edition) authored by Ustaz Zainul Mujib and to examine its conformity with the textbook development principles proposed by experts. The background of this research stems from empirical findings that demonstrate the effectiveness of khat (Arabic calligraphy) learning through the Tahsinul Kitabah al-I‘tiyādiyyah method, which is inseparable from the use of its textbook. This study employs a qualitative approach with a descriptive method and uses a library research design. The primary data were obtained through content analysis of the Tahsinul Kitabah al-I‘tiyādiyyah textbook (third edition) and interviews with the author, while secondary data were collected from relevant literature and previous studies. The results indicate that the textbook was developed based on the author’s empirical teaching experience and meets several fundamental textbook principles, including alignment with learning objectives, ease of student comprehension, the inclusion of illustrations and concrete examples, the provision of stimulating exercises, the incorporation of motivational elements, and the integration of ethical values. Methodologically, the textbook demonstrates a systematic learning sequence, the use of vertical and horizontal guide lines to explain the anatomy of letters, and the grouping of letters based on structural similarities. Therefore, the Tahsinul Kitabah al-I‘tiyādiyyah textbook can be categorized as an effective and representative learning resource that supports khat instruction in Islamic educational institutions.